Analisis Metode Economic Order Quantity (EOQ) pada Pengendalian Persediaan Kopi di Coffee Shop “Suteki” Medan - Pesta Gultom; Sarah Fadhia; Anna Annisaul Karimah; Rima Sapira; Alda Claudia Sagala (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Economic Order Quantity (EOQ) is one of the methods in inventory management used to determine the optimal order quantity to minimize total inventory costs, which include ordering costs and storage costs. This study aims to analyze the application of the EOQ model in managing inventory in a company. By using data on raw material usage, ordering costs, and storage costs, the results show that the application of EOQ can optimize the amount of purchases and order frequency more efficiently. The results of the analysis show that the application of the EOQ model contributes to reducing operational costs and increasing the effectiveness of stock management. Therefore, EOQ can be used as an appropriate inventory management strategy to support the efficiency and productivity of the company. Economic Order Quantity (EOQ) in controlling coffee inventory at the Suteki Medan Coffee Shop to minimize total inventory costs. The EOQ method is used to determine the optimal order quantity with the most efficient cost, as well as considering safety stock, reorder point, and total inventory cost.